The Dynamics of Merdeka Curriculum Change: Challenges and Opportunities in Private Madrasah Ibtidaiyah Management - Kiki Fatmawati (Universitas Islam Negeri (UIN) Salatiga, 2024)
The Indonesian government launched Merdeka curriculum policy as an attempt to update the education curriculum in Indonesia. Merdeka curriculum policy was also followed by Madrasahs under the Ministry of Religious. However, the implementation of Merdeka curriculum in Madrasahs faces a number of challenges that need to be identified. This research aims to describe the challenges and opportunities of madrasah ibtidaiyah management in Merdeka curriculum. In this study, researchers used qualitative methods by using several data collection techniques, namely observation, interviews and documentation. The data sources in this study focused on the madrasah head and teachers. The data analysis technique used Miles and Huberman. The findings of this study include challenges found in the form of 1) Lack of Resources 2) Difficulty in Teacher Understanding 3) Changes in School Culture 4) Complex Assessments. Meanwhile, the management opportunities of Madrasah Ibtidaiyah in Merdeka curriculum are 1) professional development of teachers 2) student empowerment 3) parent and community involvement 4) use of technology in learning 5) increasing student creativity. Thus, Madrasah Ibtidaiyah can take advantage of opportunities and overcome the challenges faced to remain relevant and provide quality education in accordance with the demands of the times.